Multinary positive electrode material, preparation method thereof, lithium ion battery and electric device
Patent Information
- Application Number
- CN202310632133.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-30
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-05-30
AI Technical Summary
在相同的电压下,高镍多元材料能够脱嵌出更多的锂离子,同时也意味着其晶体结构的剧烈变化,尤其在局部的过度充电会严重破会晶体结构,发生不可逆相变,导致多元材料内部产生裂纹,从而产生颗粒粉化的问题
[0028](1)本发明提供的多元正极材料包括基体和包覆在基体表面的具有特定组成的包覆层,使得钙钛矿结构的包覆层具有较高的锂离子传输能力,抑制多元正极材料与电解液(电解质)间的副反应,形成稳定的CEI膜,有利提高多元正极材料的倍率性能和循环性能,尤其进一步结合具有式II特定组成的基体,更有利于提高多元正极材料的性能;
Smart Images

Figure CN116864686B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a multi-element cathode material and its preparation method, a lithium-ion battery containing the multi-element cathode material, and an electrical device containing a lithium-ion battery. Background Technology
[0002] Lithium-ion batteries have been widely used in consumer electronic devices, and the rapid development of the new energy vehicle industry has placed higher demands on the energy density, safety, fast charging and discharging, and cycle life of power batteries. Lithium nickel manganese cobalt oxide cathode materials (referred to as high-nickel ternary materials) have become the mainstream product for high-performance lithium-ion battery cathode materials. To improve energy density, ternary materials are being developed towards high-nickel content. Under the same voltage, high-nickel ternary materials can extract and insert more lithium ions, which also means drastic changes in their crystal structure. Especially in cases of localized overcharging, the crystal structure can be severely damaged, leading to irreversible phase transitions and internal cracks in the ternary material, resulting in particle pulverization. In a high-delithiation state, the number of lithium ions in the lithium layer is greatly reduced, easily causing the collapse of the lithium layer structure, leading to the collapse of the layered structure, resulting in a significant loss of capacity and affecting the battery's cycle performance and safety.
[0003] Therefore, doping and coating techniques are particularly important for improving the structural stability and surface condition of high-nickel ternary materials. Doping and coating with alumina, zirconium oxide, titanium oxide, lithium fluoride, aluminum fluoride, and lithium phosphate can alleviate side reactions and transition metal dissolution between high-nickel ternary materials and the electrolyte, resulting in better electrochemical performance. Most coating studies focus on forming an inert or active physical isolation layer on the surface of the ternary material to reduce contact between the ternary material and the electrolyte and suppress side reactions. Research on the influence of surface stress on ternary materials is relatively limited. The large amount of residual stress caused by lithium-ion insertion / extraction can lead to lattice misalignment, stretching, and even fracture within the ternary material, manifesting as cracks and pulverization both internally and externally. This is similar to the effect of alternating loads on the fatigue of metal components, while compressive stress can effectively improve the surface hardness, wear resistance, and corrosion resistance of metals, thereby improving overall fatigue life.
[0004] Therefore, there is a need to develop a multi-element cathode material under surface compressive stress, which can be used to manufacture lithium-ion batteries with high capacity, structural stability, and long cycle life. Summary of the Invention
[0005] The purpose of this invention is to overcome the above-mentioned technical problems and provide a multi-element cathode material and its preparation method, a lithium-ion battery containing the multi-element cathode material, and an electrical device containing the lithium-ion battery. The multi-element cathode material forms a coating layer with a pressure-stabilizing phase on the surface of a nickel-based multi-element material, which suppresses excessive changes in the crystal structure of the multi-element cathode material, slows down the structural distortion caused by lithium-ion insertion / extraction, maintains a stable crystal structure, and thus improves the cycle life and safety of the lithium-ion battery.
[0006] To achieve the above objectives, a first aspect of the present invention provides a multi-element cathode material, the multi-element cathode material comprising a matrix and a coating layer covering the surface of the matrix; the matrix is a nickel-based multi-element material;
[0007] The coating layer has the composition shown in Formula I:
[0008] La 2-σ J σ Li p Al 1-p-q L q O 4-δ Formula I;
[0009] In Formula I, J is selected from at least one element among Ca, Ba, Sr, Sc, Y, Ce, Pr, Nd, Pm, Sm and Eu, L is selected from at least one element among Ni, Co, Mn, Cu and Fe, 0≤σ<1, 0<p<1, 0<q<1, p+q<1, 0≤δ<1.
[0010] Preferably, the matrix has the composition shown in Formula II:
[0011] Li z [(Ni x Co y Mn 1-x-y ) 1-α M α ] 1-β M' β O2 type II;
[0012] In Formula II, M and M' are each independently selected from at least one element selected from Al, Ba, Zr, Ti, Nb, Ta, Ga, Y, W, Ca, Sr, Sc, Cr, Mo, Hf, Si, Sm, V, La, Ce, Mg, and B; 0.9≤z≤1.3, 0<x<1, 0<y<1, x+y<1, 0<α≤0.1, 0<β≤0.1.
[0013] Preferably, the coating layer has an I4 / mmm crystal structure, and the cell parameters satisfy:
[0014] Preferably, the multi-element cathode material has a crystal structure with α-NaFeO2 of space group R-3m, and the cell parameters satisfy:
[0015] Preferably, the multi-element cathode material, as measured by XRD, exhibits characteristic diffraction peaks of the (101) and (103) crystal planes of the coating layer at 24-25.5° and 31-32.5°.
[0016] A second aspect of the present invention provides a method for preparing a multi-element cathode material, the method comprising:
[0017] Nickel-based multi-component materials are mixed as a matrix and a coating layer, followed by a first sintering, a first crushing, and a first sieving to obtain a multi-component cathode material.
[0018] The coating layer has the composition shown in Formula I:
[0019] La 2-σ J σ Li p Al 1-p-q L q O 4-δ Formula I;
[0020] In Formula I, J is selected from at least one element among Ca, Ba, Sr, Sc, Y, Ce, Pr, Nd, Pm, Sm and Eu, L is selected from at least one element among Ni, Co, Mn, Cu and Fe, 0≤σ<1, 0<p<1, 0<q<1, p+q<1, 0≤δ<1.
[0021] Preferably, the matrix is a nickel-based multi-element material having the composition shown in Formula II:
[0022] Li z [(Ni x Co y Mn 1-x-y ) 1-α M α ] 1-β M' β O2 type II;
[0023] In Formula II, M and M' are each independently selected from at least one element selected from Al, Ba, Zr, Ti, Nb, Ta, Ga, Y, W, Ca, Sr, Sc, Cr, Mo, Hf, Si, Sm, V, La, Ce, Mg, and B; 0.9≤z≤1.3, 0<x<1, 0<y<1, x+y<1, 0<α≤0.1, 0<β≤0.1.
[0024] The third aspect of this invention provides a multi-element cathode material prepared by the preparation method provided in the second aspect.
[0025] A fourth aspect of the present invention provides a lithium-ion battery, the lithium-ion battery comprising the multi-element cathode materials provided in the first and third aspects.
[0026] The fifth aspect of the present invention provides an electrical device comprising the lithium-ion battery provided in the fourth aspect.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] (1) The multi-element cathode material provided by the present invention includes a matrix and a coating layer with a specific composition on the surface of the matrix, which makes the perovskite structure coating layer have a high lithium-ion transport capacity, suppresses the side reaction between the multi-element cathode material and the electrolyte, forms a stable CEI film, and is beneficial to improve the rate performance and cycle performance of the multi-element cathode material. In particular, the combination with the matrix having the specific composition of Formula II is even more beneficial to improving the performance of the multi-element cathode material.
[0029] (2) In the multi-element cathode material provided by the present invention, the layered perovskite phase is highly matched with the crystal of the nickel-based multi-element material, so that the coating layer forms a stable chemical bond on the surface of the multi-element cathode material, that is, the coating layer and the matrix are firmly bonded.
[0030] (3) In the multi-element cathode material provided by the present invention, the cell parameter c of the coating layer is smaller than the cell parameter c of the multi-element cathode material, which suppresses the excessive expansion of the multi-element cathode material in the c-axis direction during the charging process, thereby forming compressive stress on the surface of the multi-element cathode material, suppressing excessive changes in the crystal structure, slowing down the lattice distortion caused by lithium ion deintercalation, maintaining a stable crystal structure, and thus improving the cycle life of the multi-element cathode material.
[0031] (4) In the multi-element cathode material provided by the present invention, the coating layer with layered perovskite phase has a high energy barrier, which can suppress oxygen loss from the surface of the multi-element cathode material, especially reduce oxygen loss caused by local overcharging, which is beneficial to improving the safety of the cathode material.
[0032] (5) The preparation method of the multi-element cathode material provided by the present invention is simple, feasible, practical and versatile. That is, no additional equipment is required, and it can be quickly put into use on the basis of existing equipment, making it suitable for large-scale production. Attached Figure Description
[0033] Figure 1 These are the XRD curves of the multi-element cathode materials prepared in Example 1 and Comparative Example 1;
[0034] Figure 2 This is a TEM image of the multi-element cathode material prepared in Example 1;
[0035] Figure 3 These are the initial charge-discharge curves of the multi-element cathode materials in Example 1 and Comparative Example 1 in a liquid pouch battery;
[0036] Figure 4 This is a graph showing the cycle retention rate of the multi-element cathode material in the liquid pouch battery in Example 1 and Comparative Example 1. Detailed Implementation
[0037] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0038] In this invention, unless otherwise specified, "first," "second," and "third" do not indicate a sequence or limit the specific materials or steps; they are merely used to indicate that these are not the same material or step. For example, in "first sintering," "second sintering," and "third sintering," "first," "second," and "third" are simply used to indicate that these are not the same sintering process.
[0039] The first aspect of the present invention provides a multi-element cathode material, the multi-element cathode material comprising a matrix and a coating layer covering the surface of the matrix; the matrix is a nickel-based multi-element material;
[0040] The coating layer has the composition shown in Formula I:
[0041] La 2-σ J σ Li p Al 1-p-q L q O 4-δ Formula I;
[0042] In Formula I, J is selected from at least one element among Ca, Ba, Sr, Sc, Y, Ce, Pr, Nd, Pm, Sm and Eu, L is selected from at least one element among Ni, Co, Mn, Cu and Fe, 0≤σ<1, 0<p<1, 0<q<1, p+q<1, 0≤δ<1.
[0043] In this invention, a coating layer having the composition shown in Formula I (i.e., layered perovskite La) is used. 2-σ J σ Li p Al 1-p-q L q O 4-δThe high lattice matching between the coating layer and the nickel-based multi-element material allows the coating layer to form stable chemical bonds on the surface of the multi-element cathode material, meaning that the coating layer is firmly bonded to the substrate.
[0044] In some embodiments of the present invention, preferably, in Formula I, J is selected from at least one element chosen from Sr, Y, Ce, Pr, Nd, Pm, and Sm; L is selected from at least one element chosen from Ni, Co, and Mn; 0.1 ≤ σ ≤ 0.6, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, and any value within the range of any two values; 0.4 ≤ p ≤ 0.7, for example, 0.4, 0.5, 0.6, 0.7, and any value within the range of any two values. Any value; 0.1≤q≤0.4, for example, 0.1, 0.2, 0.3, 0.4, and any value within the range of any two values; 0.5≤p+q≤0.8, for example, 0.5, 0.6, 0.7, 0.8, and any value within the range of any two values; 0≤δ<1, for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.98, and any value within the range of any two values.
[0045] In this invention, a wide range of nickel-based multi-element materials can be selected. Preferably, the matrix has the composition shown in Formula II:
[0046] Li z [(Ni x Co y Mn 1-x-y ) 1-α M α ] 1-β M' β O2 type II;
[0047] In Formula II, M and M' are each independently selected from at least one element selected from Al, Ba, Zr, Ti, Nb, Ta, Ga, Y, W, Ca, Sr, Sc, Cr, Mo, Hf, Si, Sm, V, La, Ce, Mg, and B; 0.9≤z≤1.3, 0<x<1, 0<y<1, x+y<1, 0<α≤0.1, 0<β≤0.1.
[0048] In this invention, unless otherwise specified, M and M' can be the same or different.
[0049] In some embodiments of the present invention, preferably, in Formula II, M and M' are each independently selected from at least one element selected from Al, Zr, Ti, Nb, Y, W, Sr, Mo, Hf, La, Ce, Mg, and B; 0.96 ≤ z ≤ 1.3, for example, 0.96, 1, 1.1, 1.2, 1.3, and any value within the range of any two values; 0.7 ≤ x ≤ 0.95, for example, 0.7, 0.8, 0.9, 0.93, 0.95, and any value within the range of any two values; 0.01 ≤ y ≤ 0.1, for example, 0.01, 0.02, 0.05, 0.1, and any value within a range consisting of any two numbers; 0.71≤x+y<1, for example, 0.71, 0.75, 0.8, 0.9, 0.95, and any value within a range consisting of any two numbers; 0.001≤α≤0.05, for example, 0.001, 0.005, 0.01, 0.02, 0.03, 0.05, and any value within a range consisting of any two numbers; 0.001≤β≤0.05, for example, 0.001, 0.005, 0.01, 0.02, 0.03, 0.05, and any value within a range consisting of any two numbers.
[0050] In this invention, when the coating layer and the substrate are within the above-mentioned preferred range, the selection of specific preferred doping elements, such as L and J, can enable the multi-element cathode material to have a high ionic conductivity.
[0051] In some embodiments of the present invention, preferably, the coating layer has an I4 / mmm crystal structure, and the cell parameters satisfy:
[0052] In some embodiments of the present invention, preferably, the multi-element cathode material has a crystal structure with an α-NaFeO2 structure having an R-3m space group, and the cell parameters satisfy:
[0053] In this invention, the crystal structure and cell parameters of the coating layer and the multi-element cathode material were measured using a Rigaku X-ray diffractometer.
[0054] In this invention, the cell parameters of the coating layer and the multi-element cathode material with the composition shown in Formula I are relatively close, with the c-values being even closer. However, the c-value of the coating layer is smaller than that of the multi-element cathode material. This allows the coating layer to generate compressive stress on the substrate during charge-discharge processes as the multi-element cathode material expands, suppressing excessive changes in the crystal structure of the multi-element cathode material, mitigating structural distortion caused by lithium-ion insertion / extraction, maintaining a stable crystal structure, and improving the cycle life of the multi-element cathode material. In other words, based on the specific elemental composition and specific cell parameter range in the coating layer with the composition shown in Formula I, not only can the ionic conductivity be improved, but the cycle life can also be increased.
[0055] In some embodiments of the present invention, preferably, based on the mass of the substrate, the content of the coating layer is 0.01-2 wt%, for example, 0.01 wt%, 0.1 wt%, 0.2 wt%, 0.33 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, and any value within any range of any two values, preferably 0.1-1 wt%. A coating layer satisfying the above content range is more conducive to improving the capacity performance and cycle performance of the multi-element cathode material.
[0056] In some embodiments of the present invention, preferably, the ionic conductivity of the coating layer is ≥0.3 mS / cm, more preferably 0.4-1 mS / cm. In this invention, the ionic conductivity parameter is obtained by measuring the AC impedance of a blockage electrode assembled with a composite solid electrolyte, and calculated using the formula ionic conductivity = L / RS, where L is the thickness of the composite solid electrolyte (cm); R is the impedance value (unit); and S is the effective electrode area (cm²). 2 .
[0057] In some embodiments of the present invention, preferably, the thickness of the coating layer is 2-20 nm, for example, 2 nm, 5 nm, 8 nm, 10 nm, 15 nm, 20 nm, or any value within the range of any two values, preferably 5-10 nm. In the present invention, the thickness parameter is measured using a Hitachi HF5000 transmission electron microscope.
[0058] In some embodiments of the present invention, preferably, the median particle size D of the coating layer is... 50 ≤200nm, for example, 10nm, 20nm, 50nm, 80nm, 100nm, 150nm, 200nm, and any value within the range of any two values, preferably 10-150nm; specific surface area ≥10m² 2 / g, for example, 10m 2 / g、20m 2 / g, 50m 2 / g、80m 2 / g, 100m2 / g, 150m 2 / g、200m 2 / g、300m 2 / g、400m 2 / g、500m 2 / g, and any value within the range of any two values, preferably 20-500m. 2 / g. In this invention, by using a coating layer within the above-mentioned range, effective compressive stress can be formed on the surface of the positive electrode material, suppressing volume expansion during charging and discharging; moreover, while suppressing side reactions between the positive electrode material and the electrolyte material, it does not affect charge transfer during charging and discharging.
[0059] In this invention, particle size (D) 50 D 100 The parameters were measured using a Mastersizer 3000 laser particle size analyzer; the specific surface area parameter was measured using a Micron 3030 ratio meter.
[0060] In some embodiments of the present invention, preferably, the median particle size D of the multi-element cathode material is... 50 The value is 2-30 μm, for example, 2 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 30 μm, and any value within the range of any two values, preferably 3-20 μm.
[0061] In some embodiments of the present invention, preferably, the multi-element cathode material, as measured by XRD, exhibits characteristic diffraction peaks of the (101) and (103) crystal planes of the coating layer at 24-25.5° and 31-32.5°. When the above conditions are met, it indicates that a coating layer with the composition of Formula I is formed on the surface of the multi-element cathode material, and after heat treatment with the nickel-based multi-element material, a solid solution is formed by the reaction, which causes a slight change in the coating layer material, that is, changes in the surface properties of the multi-element cathode material.
[0062] In some embodiments of the present invention, preferably, the characteristic peak intensity I of the (103) crystal plane of the multi-element cathode material as measured by XRD is... (103) The characteristic peak intensity I of the (003) crystal plane (003) The following relationship must be satisfied: 0.0001 < I (103) / I (003) <0.005, for example, I (103) / I (003) The value is selected from 0.0012, 0.0014, 0.0015, 0.0018, 0.0021, 0.0072, and any value within the range of any two values. Preferably, 0.001 < 1. (103) / I (003)<0.003; and, the characteristic peak area S of the (103) crystal plane of the multi-element cathode material as measured by XRD. (103) The characteristic peak area S of the (003) crystal plane (003) The following relationship must be satisfied: 0.0001 < S (103) / S (003) <0.005, for example, S (103) / S (003) The value is selected from 0.0002, 0.0008, 0.0012, 0.0019, 0.0021, 0.0022, 0.0026, 0.0041, and any value within the range of any two values. Preferably, 0.0001 < S. (103) / S (003) <0.003.
[0063] In this invention, when I (103) / I (003) and S (103) / S (003) When all of the above ranges are met, it indicates that the matrix and coating of the multi-element cathode material have undergone solid solution, characterizing the strength of their bonding. This can suppress volume changes during lithium-ion insertion / extraction, reduce pulverization caused by electrolyte intrusion into material gaps, and thus improve the cycle life of the multi-element cathode material in the battery. Additionally, when I... (103) / I (003) and S (103) / S (003) When all of the above ranges are met, after the substrate is modified by the coating layer, a solid solution with compressive stress is formed only on the surface, which still has a high degree of crystallinity, characterizing the good crystal structure of the surface of the multi-element cathode material, which facilitates the lithium ion insertion and extraction reaction.
[0064] In some embodiments of the present invention, preferably, when the molar percentage x of Ni in the matrix satisfies 0.3 < x ≤ 0.98, the maximum change value Δc of the unit cell along the c-axis direction of the multi-element cathode material during charging and discharging is... max satisfy: Where, Δc max =c max -c min c max and c min These represent the maximum and minimum values of the unit cell along the c-axis, respectively. x represents the molar percentage of Ni in the matrix. In this invention, Δc max Meeting the above range indicates that a firmly bonded perovskite structure coating layer is formed on the surface of the multi-electrode cathode material, which suppresses side reactions between the multi-electrode cathode material and the electrolyte and can maintain the crystal structure of the multi-electrode cathode material during the lithium insertion / extraction process.
[0065] In some embodiments of the present invention, preferably, when the molar percentage x of Ni in the matrix satisfies 0.3 < x ≤ 0.98, the maximum rate of change of the c-axis of the multi-element cathode material during charging and discharging is... satisfy: c0 is the initial value of the unit cell along the c-axis direction. x represents the molar percentage of Ni in the matrix. In this invention, Meeting the above range indicates that the perovskite structure coating layer on the surface of the multi-element cathode material can form compressive stress during charging and discharging, which can mitigate the lattice distortion caused by lithium ion insertion / extraction and improve the crystal structure stability during cycling.
[0066] In some embodiments of the present invention, preferably, when the molar percentage x of Ni in the matrix satisfies 0.3 < x ≤ 0.98, the maximum change in shear strain of the multi-element cathode material during charging and discharging is... satisfy: in, x represents the molar percentage of Ni in the matrix.
[0067] In this invention, Meeting the above range indicates that the perovskite structure coating layer on the surface of the multi-element cathode material can rapidly transport lithium ions, thereby improving the rate performance and cycle performance of the multi-element cathode material.
[0068] In some embodiments of the present invention, preferably, when the molar percentage x of Ni in the matrix satisfies 0.3 < x ≤ 0.98, the maximum rate of change of shear strain of the multi-element cathode material during charging and discharging is... satisfy: Where (c / a)0 is the initial shear strain, and x is the molar percentage of Ni in the matrix.
[0069] In this invention, If the above range is met, the perovskite structure coating layer on the surface of the multi-element cathode material has a high energy barrier, which can suppress oxygen loss from the surface of the multi-element cathode material and improve the thermal stability of the multi-element cathode material.
[0070] In this invention, the c and a values in the multi-element cathode material can be calculated based on XRD patterns and unit cell volume formulas. During the charging and discharging process of the multi-element cathode material, the a and c values change simultaneously, where c / a represents the shear strain in the material during charging and discharging. and When all parameters meet this range, the volume change of the multi-element cathode material is small at the same lithium insertion / extraction amount, which means it has a stable structure and is beneficial to improving cycle performance.
[0071] In some embodiments of the present invention, the Δc max and The measurement conditions are that the molar amount of lithium removed from the multi-element cathode material, Δz, is in the range of 0 < Δz < 0.9, where Δz is the amount of lithium ions removed from the multi-element cathode material during charging.
[0072] The second aspect of the present invention provides a method for preparing a multi-element cathode material, the method comprising: mixing a nickel-based multi-element material as a matrix and a coating layer, performing a first sintering, a first crushing, and a first sieving to obtain the multi-element cathode material;
[0073] The coating layer has the composition shown in Formula I: La 2-σ J σ Li p Al 1-p-q L q O 4-δ Formula I;
[0074] In Formula I, J is selected from at least one element among Ca, Ba, Sr, Sc, Y, Ce, Pr, Nd, Pm, Sm and Eu, L is selected from at least one element among Ni, Co, Mn, Cu and Fe, 0≤σ<1, 0<p<1, 0<q<1, p+q<1, 0≤δ<1.
[0075] In some embodiments of the present invention, preferably, in Formula I, J is selected from at least one element chosen from Sr, Y, Ce, Pr, Nd, Pm, and Sm; L is selected from at least one element chosen from Ni, Co, and Mn; 0.1 ≤ σ ≤ 0.6, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, and any value within the range of any two values; 0.4 ≤ p ≤ 0.7, for example, 0.4, 0.5, 0.6, 0.7, and any value within the range of any two values. Any value; 0.1≤q≤0.4, for example, 0.1, 0.2, 0.3, 0.4, and any value within the range of any two values; 0.5≤p+q≤0.8, for example, 0.5, 0.6, 0.7, 0.8, and any value within the range of any two values; 0≤δ<1, for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.98, and any value within the range of any two values.
[0076] In some embodiments of the present invention, preferably, the matrix is a nickel-based multi-element material having the composition shown in Formula II: Li z [(Ni x Co y Mn 1-x-y ) 1-α Mα ] 1-β M' β O2 type II;
[0077] In Formula II, M and M' are each independently selected from at least one element selected from Al, Ba, Zr, Ti, Nb, Ta, Ga, Y, W, Ca, Sr, Sc, Cr, Mo, Hf, Si, Sm, V, La, Ce, Mg, and B; 0.9≤z≤1.3, 0<x<1, 0<y<1, x+y<1, 0<α≤0.1, 0<β≤0.1.
[0078] In some embodiments of the present invention, more preferably, in Formula II, M and M' are each independently selected from at least one element selected from Al, Zr, Ti, Nb, Y, W, Sr, Mo, Hf, La, Ce, Mg, and B; 0.96 ≤ z ≤ 1.3, for example, 0.96, 1, 1.1, 1.2, 1.3, and any value within the range of any two values; 0.7 ≤ x ≤ 0.95, for example, 0.7, 0.8, 0.9, 0.93, 0.95, and any value within the range of any two values; 0.01 ≤ y ≤ 0.1, for example, 0.01, 0.02, 0.0 5, 0.1, and any value within a range consisting of any two numbers; 0.71≤x+y<1, for example, 0.71, 0.75, 0.8, 0.9, 0.95, and any value within a range consisting of any two numbers; 0.001≤α≤0.05, for example, 0.001, 0.005, 0.01, 0.02, 0.03, 0.05, and any value within a range consisting of any two numbers; 0.001≤β≤0.05, for example, 0.001, 0.005, 0.01, 0.02, 0.03, 0.05, and any value within a range consisting of any two numbers.
[0079] In some embodiments of the present invention, preferably, the mass ratio of the substrate to the coating layer is 100:0.01-2, for example, 100:0.01, 100:0.1, 100:0.2, 100:0.33, 100:0.5, 100:1, 100:1.5, 100:2, and any value within any range of two such values, preferably 100:0.1-1. In the present invention, using the above-mentioned mass ratio range enables the formation of a continuous coating layer on the substrate surface, reducing lattice expansion caused by lithium-ion insertion / extraction, suppressing electrolyte corrosion, and improving the cycle life of the multi-element cathode material.
[0080] In some embodiments of the present invention, preferably, the conditions for the first sintering include: a temperature of 270-620°C, more preferably 300-580°C; and a time of 4-48 hours, more preferably 8-24 hours.
[0081] In this invention, the first crushing and the first screening are aimed at obtaining the median particle size D. 50 The cathode material has a diameter of 2-30 μm, preferably 3-20 μm. In this invention, the first crushing can be achieved by roller crushing, ball milling, air jet milling, or mechanical milling; the first screening can be achieved by ultrasonic vibrating screen.
[0082] In this invention, there is a wide range of options for preparing the coating layer, as long as the coating layer meets the above-mentioned limitations. Preferably, the coating layer is obtained by high-temperature solid-state treatment.
[0083] In some embodiments of the present invention, preferably, the coating layer is prepared according to the following steps:
[0084] (1) The lanthanum source, J source, lithium source, aluminum source and L source are mixed in a molar ratio of n(La):n(J):n(Li):n(Al):n(L)=(2-σ):σ:p:(1-pq):q to obtain a mixture;
[0085] (2) The mixture is subjected to a first wet milling, a first drying, a second sintering, a second wet milling, a second drying, and a second crushing in sequence to obtain the coating layer.
[0086] In some embodiments of the present invention, preferably, the lanthanum source is selected from at least one of lanthanum oxide, lanthanum hydroxide, and lanthanum carbonate; the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium nitrate; the aluminum source is selected from at least one of aluminum oxide and aluminum hydroxide; and the J source and L source are each independently selected from at least one of oxides, hydroxides, or carbonates containing J and L.
[0087] In one specific embodiment of the present invention, the J source is selected from at least one of oxides, hydroxides or carbonates containing Ca, Ba, Sr, Sc, Y, Ce, Pr, Nd, Pm, Sm and Eu, preferably selected from at least one of oxides, hydroxides or carbonates containing Sr, Y, Ce, Pr, Nd, Pm and Sm; the L source is selected from at least one of oxides, hydroxides or carbonates containing Ni, Co, Mn, Cu and Fe, preferably selected from at least one of oxides, hydroxides or carbonates containing Ni, Co and Mn.
[0088] In some embodiments of the present invention, preferably, in step (1), the ratio of the amount of lanthanum source, J source, lithium source, aluminum source and L source satisfies n(La):n(J):n(Li):n(Al):n(L), wherein 1 < n(La) ≤ 2, 0 ≤ n(J) < 1, 0 < n(Li) < 1, 0 < n(Al) < 1, 0 < n(L) < 1; more preferably, 1.4 ≤ n(La) ≤ 1.9, 0.1 ≤ n(J) ≤ 0.6, 0.4 ≤ n(Li) ≤ 0.7, 0.2 ≤ n(Al) ≤ 0.5, 0.1 ≤ n(L) ≤ 0.4.
[0089] In some embodiments of the present invention, preferably, in step (1), the amount of lithium source, calculated as Li, is n(Li) = (1.03-1.1)×p, for example, 1.03p, 1.05p, 1.08p, 1.1p, and any value within the range of any two values. When the amount of lithium source meets the above range, it can not only compensate for the partial volatilization of the L source during the high-temperature sintering process, but also improve the ionic conductivity of the obtained coating layer.
[0090] In some embodiments of the present invention, preferably, in step (2), the first wet milling process includes: performing a first wet milling on the mixture, the first dispersant and the first solvent to obtain a first wet milling slurry; the second wet milling process includes: performing a second wet milling on the second sintered product, the second dispersant and the second solvent to obtain a second wet milling slurry.
[0091] In some embodiments of the present invention, preferably, in step (2), the mass ratio of the mixture to the first dispersant is 100:0.001-5, for example, 100:0.001, 100:0.005, 100:0.01, 100:0.05, 100:0.1, 100:0.5, 100:1, 100:2, 100:5, and any value within a range of any two values, preferably 10. The mass ratio of the second sintered product to the second dispersant is 100:0.001-5, for example, 100:0.001, 100:0.005, 100:0.01, 100:0.05, 100:0.1, 100:0.5, 100:1, 100:2, 100:5, and any value within any range of two values, preferably 100:0.005-2. Using the first and second dispersants within the above range not only improves grinding efficiency but also yields a coating material with good dispersibility.
[0092] In some embodiments of the present invention, preferably, the first dispersant and the second dispersant are each independently selected from dispersants with a weight-average molecular weight of 400-5000 g / mol, and more preferably from polyacrylates and / or polyethylene glycol. In the present invention, polyacrylates include, but are not limited to, ammonium polyacrylate, polyamine-2-butoxyethanol, etc.
[0093] In some embodiments of the present invention, preferably, the first solvent is selected from water and / or an organic solvent, wherein the organic solvent is selected from at least one of ethanol, acetone and N-methylpyrrolidone; the second solvent is selected from an organic solvent, preferably from at least one of ethanol, acetone and N-methylpyrrolidone.
[0094] In some embodiments of the present invention, preferably, the particle size D of the first wet grinding slurry is... 50 <5μm, D 100 <20μm; more preferably, the particle size D of the first wet grinding slurry 50 <0.5μm, D 100 <1μm.
[0095] In some embodiments of the present invention, preferably, the particle size D of the second wet grinding slurry is... 50 <0.5μm, D 100 <1μm; more preferably, the particle size D of the second wet grinding slurry 50 <0.2μm, D 100 <0.5μm. When the above relationship is satisfied, the median particle size D of the coating layer is such that... 50 ≤200nm, specific surface area ≥10m² 2 / g, while maintaining a stable I4 / mmm crystal structure, at which point it has high ionic conductivity.
[0096] In this invention, in step (2), the first drying aims to remove the first solvent to obtain a first dried powder. Preferably, the inlet air temperature of the first drying is 140-280°C, and the outlet air temperature is 60-130°C. In this invention, the first drying includes, but is not limited to, spray drying, flash drying, etc.
[0097] In this invention, in step (2), the second sintering aims to obtain a coating layer with a specific composition and crystal structure. Preferably, the conditions for the second sintering include: a temperature of 700-1300℃, more preferably 800-1100℃; and a time of 8-24h, more preferably 10-16h.
[0098] In this invention, in step (2), the second drying aims to remove the second solvent to obtain a second dried powder. Preferably, the inlet air temperature of the second drying is 160-260°C, and the outlet air temperature is 75-110°C. In this invention, the second drying includes, but is not limited to, spray drying, flash drying, etc.
[0099] In this invention, in step (2), the type of material to be crushed has a wide selection range, as long as it can produce a loose, free-flowing powder. The second crushing can be achieved by roller crushing, ball milling, air jet milling, or mechanical milling.
[0100] In some embodiments of the present invention, preferably, the nickel-based multi-element material is obtained according to the following steps:
[0101] S1. Prepare a mixed salt solution by mixing nickel salt, cobalt salt, and manganese salt in a molar ratio of n(Ni):n(Co):n(Mn)=x:y:(1-xy); prepare M source, precipitant, and complexing agent into M source solution, precipitant solution, and complexing agent solution, respectively.
[0102] S2. The mixed salt solution, M source solution, precipitant solution and complexing agent solution are added to the reaction vessel, and a co-precipitation reaction is carried out in an inert atmosphere. The resulting solid-liquid mixed slurry is filtered, washed, dried in the third stage and screened in the second stage. The resulting multi-component material precursor has the composition shown in Formula III.
[0103] S3. The multi-component material precursor, lithium source and M' source are mixed, sintered, crushed and screened in the third step to obtain nickel-based multi-component material;
[0104] Among them, [(Ni x Co y Mn 1-x-y ) 1-α M α Formula III (OH)2;
[0105] In some embodiments of the present invention, preferably, in step S1, the concentration of the mixed salt solution, calculated as metal, is 1-3 mol / L, for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, or any value within the range of any two values, preferably 1.5-2.5 mol / L; the concentration of the precipitant solution is 2-15 mol / L, for example, 2 mol / L, 5 mol / L, 8 mol / L, 10 mol / L, 15 mol / L, or any value within the range of any two values, preferably 5-10 mol / L. / L; the concentration of the complexing agent solution is 1-15 mol / L, for example, 1 mol / L, 5 mol / L, 8 mol / L, 10 mol / L, 15 mol / L, and any value within the range of any two values, preferably 5-10 mol / L; the concentration of the M source solution, calculated as M, is 0.01-1 mol / L, for example, 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.5 mol / L, 1 mol / L, and any value within the range of any two values, preferably 0.05-0.5 mol / L.
[0106] In some embodiments of the present invention, preferably, in step S1, the nickel salt, cobalt salt, and manganese salt are each independently selected from at least one of sulfates, nitrates, chlorides, oxalates, acetates, and citrates containing nickel, cobalt, and manganese; more preferably, the nickel salt is selected from at least one of nickel sulfate, nickel nitrate, nickel chloride, nickel oxalate, nickel acetate, and nickel citrate; the cobalt salt is selected from at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt oxalate, cobalt acetate, and cobalt citrate; and the manganese salt is selected from at least one of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, manganese acetate, and manganese citrate.
[0107] In one specific embodiment of the present invention, in step S1, the ratio of the amount of nickel salt, cobalt salt and manganese salt satisfies n(Ni):n(Co):n(Mn), wherein 0 < n(Ni) < 1, 0 < n(Co) < 1, 0 < n(Mn) < 1; preferably, 0.75 ≤ n(Ni) ≤ 0.95, 0.01 ≤ n(Co) ≤ 0.1, 0 < n(Mn) ≤ 0.29.
[0108] In some embodiments of the present invention, preferably, in step S1, the M source is selected from at least one of oxides, hydroxides and carbonates containing M, wherein M is selected from at least one element selected from Al, Ba, Zr, Ti, Nb, Ta, Ga, Y, W, Ca, Sr, Sc, Cr, Mo, Hf, Si, Sm, V, La, Ce, Mg and B, and more preferably from at least one element selected from Al, Zr, Ti, Nb, Y, W, Sr, Mo, Hf, La, Ce, Mg and B; more preferably, the M source is selected from at least one of sodium aluminate, barium nitrate, zirconium nitrate, zirconium chloride, titanium sulfate, niobium nitrate, tantalum nitrate, gallium nitrate, yttrium nitrate, ammonium tungstate, calcium chloride, lanthanum nitrate, cerium nitrate, magnesium nitrate and sodium borate.
[0109] In some embodiments of the present invention, preferably, in step S1, the M source is added in a molar ratio of 0 < [n(M)] / [n(Ni)+n(Co)+n(Mn)] ≤ 0.1, and more preferably in a molar ratio of 0.001 ≤ [n(M)] / [n(Ni)+n(Co)+n(Mn)] ≤ 0.05. In the present invention, when the amount of the M source meets the above range, the M element can effectively enter the lattice of the multi-element material precursor, fine-tuning the lattice parameters of the multi-element material to obtain a more fatigue-resistant crystal structure, while not severely causing lattice distortion that alters the structure and hinders lithium-ion transport.
[0110] In some embodiments of the present invention, preferably, in step S1, the precipitant includes, but is not limited to, sodium hydroxide and / or potassium hydroxide; the complexing agent includes, but is not limited to, ammonia, sodium ethylenediaminetetraacetate, ammonium nitrate, ammonium chlorate, ammonium sulfate, etc. In the present invention, the amount of the precipitant and complexing agent is not particularly limited and can be controlled according to the morphology and particle size of the multi-component material precursor.
[0111] In some embodiments of the present invention, preferably, in step S2, the conditions for the coprecipitation reaction include: a pH value of 10-13, preferably 11-12; a temperature of 40-80℃, preferably 50-70℃; and a time of 5-50h, preferably 8-32h.
[0112] In some embodiments of the present invention, preferably, in step S2, the particle size D of the multi-component material precursor is... 50 The value is 2-30 μm, for example, 2 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 30 μm, and any value within the range of any two values, preferably 3-20 μm.
[0113] In some embodiments of the present invention, in step S2, the multi-component material precursor has the composition shown in Formula III, wherein [(Ni x Coy Mn 1-x-y ) 1-α M α Formula III (OH)2; wherein M is selected from at least one element selected from Al, Ba, Zr, Ti, Nb, Ta, Ga, Y, W, Ca, Sr, Sc, Cr, Mo, Hf, Si, Sm, V, La, Ce, Mg and B; 0 < x < 1, 0 < y < 1, x + y < 1, 0 < α ≤ 0.1; preferably, M is selected from at least one element selected from Al, Zr, Ti, Nb, Y, W, Sr, Mo, Hf, La, Ce, Mg and B; 0.7 ≤ x ≤ 0.95, 0.01 ≤ y ≤ 0.1, 0.71 ≤ x + y < 1.
[0114] In this invention, the filtration in step S2 is intended to remove liquid from the solid-liquid mixture, and the filtration includes, but is not limited to, suction filtration, pressure filtration, centrifugation, etc.; the washing is intended to remove residual impurities in the filtered product; the third drying is intended to remove residual moisture in the washed product, including, but not limited to, hot air drying, infrared drying, microwave drying, etc.; the second sieving is intended to obtain a multi-component material precursor with a specific particle size range.
[0115] In some embodiments of the present invention, preferably, in step S3, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium nitrate; the M' source is selected from at least one of oxides, hydroxides, and carbonates containing M', and M' is selected from at least one element selected from Al, Ba, Zr, Ti, Nb, Ta, Ga, Y, W, Ca, Sr, Sc, Cr, Mo, Hf, Si, Sm, V, La, Ce, Mg, and B, preferably selected from at least one element selected from Al, Zr, Ti, Nb, Y, W, Sr, Mo, Hf, La, Ce, Mg, and B; more preferably, the M' source is selected from at least one of sodium aluminate, barium nitrate, zirconium nitrate, zirconium chloride, titanium sulfate, niobium nitrate, tantalum nitrate, gallium nitrate, yttrium nitrate, ammonium tungstate, calcium chloride, lanthanum nitrate, cerium nitrate, magnesium nitrate, and sodium borate.
[0116] In some embodiments of the present invention, preferably, in step S3, the lithium source is added in an amount with a molar ratio of 0.9 ≤ n(Li) / [n(Ni)+n(Co)+n(Mn)+n(M)+n(M')] ≤ 1.3, and more preferably in an amount of 0.96 ≤ n(Li) / [n(Ni)+n(Co)+n(Mn)+n(M)+n(M')] ≤ 1.3. When the amount of lithium source meets the above range, a nickel-based multi-element material with an R-3m space group and a complete α-NaFeO2 structure can be formed, giving it a high specific capacity.
[0117] In some embodiments of the present invention, preferably, in step S3, the M' source is added in a molar ratio of 0 < n(M') / [n(Ni)+n(Co)+n(Mn)] ≤ 0.1, and more preferably in a molar ratio of 0.001 ≤ n(M') / [n(Ni)+n(Co)+n(Mn)] ≤ 0.05. In the present invention, when the amounts of the M' source and the multi-element precursor meet the above ranges, the M' element can effectively stabilize the crystal structure and improve cycle stability.
[0118] In some embodiments of the present invention, preferably, in step S3, the median particle size D of the M' source is... 50 ≤200nm, preferably 10-150nm; specific surface area ≥10m² 2 / g, preferably 50-500m 2 / g. In this invention, the M' source satisfies the above-described specifications, ensuring that the M' source and the multi-component material precursor are mixed uniformly.
[0119] In some embodiments of the present invention, preferably, in step S3, the conditions for the third sintering include: a sintering temperature of 650-1000℃, preferably 800-950℃; and a sintering time of 4-48h, preferably 8-24h.
[0120] In this invention, in step S3, the lithium salt mixed with the multi-element material precursor is a soft powder. After the third sintering, the volume shrinks, forming a block with higher hardness. Therefore, a third crushing and third sieving are required to obtain nickel-based multi-element material powder of the appropriate particle size, which also facilitates the subsequent coating process. In this invention, the third crushing can be achieved by roller crushing, ball milling, air jet milling, or mechanical milling; the third sieving can be achieved by ultrasonic vibrating screen.
[0121] The third aspect of this invention provides a multi-element cathode material prepared by the preparation method provided in the second aspect.
[0122] A fourth aspect of the present invention provides a lithium-ion battery, the lithium-ion battery comprising: the positive electrode materials provided in the first aspect and the third aspect.
[0123] A fifth aspect of this invention provides an electrical device, which includes the lithium-ion battery provided in the fourth aspect. In this invention, the electrical device includes, but is not limited to, automobiles, mobile phones, tablet computers, laptops, flashlights, digital cameras, digital camcorders, engineering lighting fixtures, emergency lights, electric toys, game consoles, power tools, small household appliances, portable audio-visual digital devices, instruments, balance scooters, starting power supplies, or energy storage systems.
[0124] The present invention will be described in detail below through embodiments. In the following embodiments,
[0125] Particle size parameters were measured using a Mastersizer 3000 laser particle size analyzer;
[0126] The crystal structure (XRD) was determined using a Rigaku X-ray diffractometer;
[0127] The thickness parameters were measured using a Hitachi HF5000 transmission electron microscope;
[0128] The ionic conductivity was obtained by measuring the AC impedance of a blockage electrode assembled with a composite solid electrolyte and calculated using the formula: ionic conductivity = L / RS, where L is the thickness of the composite solid electrolyte, R is the impedance value, and S is the effective electrode area.
[0129] The specific surface area parameter was measured using a Mc3030 ratio meter.
[0130] The weight-average molecular weight of ammonium polyacrylate is 4200 g / mol;
[0131] The weight-average molecular weight of polyamine amide-2-butoxyethanol is 3500 g / mol.
[0132] Preparation Example 1
[0133] (1) The lanthanum source (La2O3), lithium source (LiOH·H2O), aluminum source (Al2O3) and L source (Co(OH)2) are mixed in a molar ratio of n(La):n(Li):n(Al):n(L)=2:0.5:0.3:0.2 to obtain a mixture;
[0134] (2) The above mixture, the first dispersant (ammonium polyacrylate), and the first solvent (water) are mixed and subjected to a first wet milling (2000 rpm for 2 hours) to obtain the particle size D of the first wet milled slurry. 50 =0.2μm, D 100 =0.8μm, wherein the mass ratio of the above mixture to the first dispersant is 100:0.15;
[0135] The first wet milling slurry was subjected to a first drying process (inlet air temperature 220℃, outlet air temperature 100℃), and the resulting first dried powder was subjected to a second sintering process (temperature 835℃, time 10h). The resulting second sintered product, the second dispersant (polyamine-2-butoxyethanol with a weight average molecular weight of 2000 g / mol), and the second solvent (ethanol) were subjected to a second wet milling process (speed 2500 rpm, time 4h) to obtain the particle size D of the second wet milling slurry. 50 =0.03μm, D 100 =0.1μm, wherein the mass ratio of the second sintered product and the second dispersant is 100:0.5;
[0136] The second wet grinding slurry was subjected to a second drying process (inlet air temperature 120℃, outlet air temperature 75℃) and crushed to obtain the general formula La2Li. 0.5 Al 0.3 Co 0.2 O4 coating layer C1.
[0137] The physical properties of the aforementioned coating layer C1 are listed in Table 2.
[0138] Preparation Example 2
[0139] Following the method of Preparation Example 1, except that, according to the process parameters in Table 1, the general formula La2Li was obtained. 0.5 Al 0.4 Co 0.1 O4 coating layer C2;
[0140] The physical properties of the aforementioned coating layer C2 are listed in Table 2.
[0141] Preparation Example 3
[0142] Following the method of Preparation Example 1, except that, according to the process parameters in Table 1, the general formula La was obtained. 1.5 Sr 0.5 Li 0.5 Al 0.3 Co 0.2 O4 coating layer C3;
[0143] The physical properties of the aforementioned coating layer C3 are listed in Table 2.
[0144] Preparation Example 4
[0145] Following the method of Preparation Example 1, except that, according to the process parameters in Table 1, the general formula La2Li was obtained. 0.8 Al 0.15 Co 0.05 O4 coating layer C4;
[0146] The physical properties of the aforementioned coating layer C4 are listed in Table 2.
[0147] Preparation Example 5
[0148] Following the method of Preparation Example 1, except that, according to the process parameters in Table 1, the general formula La2Li was obtained. 0.5 Al 0.3 Cu 0.2 O4 coating layer C5;
[0149] The physical properties of the aforementioned coating layer C5 are listed in Table 2.
[0150] Preparation Example 6
[0151] Following the method of Preparation Example 3, except that, according to the process parameters in Table 1, the general formula La was obtained. 1.5 Ca 0.5 Li 0.5 Al 0.3 Co 0.2 O4 coating layer C6;
[0152] The physical properties of the aforementioned coating layer C6 are listed in Table 2.
[0153] Preparation Example 7
[0154] Following the method of Preparation Example 1, except that, according to the process parameters in Table 1, the general formula La2Li was obtained. 0.5 Al 0.5 O4 coating layer DC1.
[0155] The physical properties of the aforementioned coating layer DC1 are listed in Table 2.
[0156] Preparation Example 8
[0157] Following the method of Preparation Example 1, except that, according to the process parameters in Table 1, the general formula La2Li was obtained. 0.5 Co 0.5 O4 coating layer DC2.
[0158] The physical properties of the aforementioned coating layer DC2 are listed in Table 2.
[0159] Preparation Example 9
[0160] Following the method of Preparation Example 1, except that, according to the process parameters in Table 1, a coating layer DC3 with the general formula LaSrAlO4 was obtained.
[0161] The physical properties of the aforementioned coating layer DC3 are listed in Table 2.
[0162] Table 1
[0163]
[0164]
[0165] Note: 1 - Mass ratio of the first dispersant to the mixture; 2 - Mass ratio of the second dispersant to the second sintered product.
[0166] Continued from Table 1
[0167]
[0168] Continued from Table 1
[0169]
[0170]
[0171] Table 2
[0172]
[0173] As can be seen from the results in Table 1-2, compared with preparation examples 7-9, the coating layers obtained in preparation examples 1-6 satisfy the composition shown in I: La 2-σ J σ Li p Al 1-p-q L q O 4-δ (I) simultaneously possesses an I4 / mmm crystal structure, with unit cell parameters satisfying: This gives the coating material a high ionic conductivity, thereby improving the capacity and rate capability of the multi-element cathode material.
[0174] Meanwhile, compared to preparation examples 4-6, preparation examples 1-3 adopted a scheme in Formula I where each subscript and metal element is within the preferred protection range, which makes the multi-element cathode material have higher ionic conductivity, thereby improving capacity and rate capability.
[0175] Example 1
[0176] S1. Based on the metal element, prepare a mixed salt solution with a concentration of 2 mol / L by mixing nickel salt (nickel sulfate), cobalt salt (cobalt sulfate) and manganese salt (manganese sulfate) in a molar ratio of 93:2:5; prepare M source (aluminum sulfate), precipitant (sodium hydroxide) and complexing agent (ammonia) into M source solutions with concentrations of 0.1 mol / L, precipitant solutions with concentrations of 2 mol / L and complexing agent solutions with concentrations of 6 mol / L, respectively.
[0177] S2. Add the above mixed salt solution, M source solution, precipitant solution, and complexing agent solution to the reactor, and carry out a co-precipitation reaction under an inert atmosphere (pH 11.2-11.8, temperature 60℃) to obtain a solid-liquid mixed slurry with a particle size D. 50 It is 4μm;
[0178] Among them, source M is added in a molar ratio of [n(M)] / [n(Ni)+n(Co)+n(Mn)]=0.001;
[0179] The above solid-liquid mixture was sequentially filtered, washed, dried, and sieved to obtain the general formula [(Ni 0.93 Co 0.02 Mn 0.05 ) 0.999 Al 0.001 Multi-component precursors of (OH)2;
[0180] S3, combine the above-mentioned multi-component precursor material, lithium source (lithium hydroxide), and M' source (zirconia, D) 50 It has a wavelength of 50nm and a specific surface area of 100m². 2 The mixture of / g) is subjected to a third sintering (temperature 835℃, time 12h), a third crushing, and a third sieving to obtain nickel-based multi-component materials;
[0181] The lithium source is added in a molar ratio of [n(Li)] / [n(Ni)+n(Co)+n(Mn)+n(M)+n(M')] = 1.03; the M' source is added in a molar ratio of [n(M')] / [n(Ni)+n(Co)+n(Mn)] = 0.001; the general formula of the above nickel-based ternary material is Li 1.03 [(Ni 0.93 Co 0.02 Mn 0.05 ) 0.999 Al 0.001 ] 0.999 Zr 0.001 O2;
[0182] S4. The above nickel-based multi-element material is used as the matrix and the above coating layer C1 are mixed at a mass ratio of 100:0.33 and subjected to a first sintering (temperature of 400℃, time of 8h), crushed and sieved to obtain multi-element cathode material Q1.
[0183] The XRD curve of the aforementioned multi-element cathode material Q1 is shown below. Figure 1 As shown, by Figure 1 It can be seen that the 2θ of the multi-element cathode material Q1 exhibits characteristic diffraction peaks of the (101) and (103) crystal planes of the aforementioned coating layer C1 at 24-25.5° and 31-32.5°; simultaneously, I (103) / I (003) =0.0018, S (103) / S (003) =0.0026, indicating that solid solution has occurred between the matrix and the coating layer C1, forming a compressive stress solid solution on the surface. At the same time, the multi-element cathode material still has high crystallinity and maintains a stable crystal structure, which facilitates the lithium ion insertion and extraction reaction.
[0184] The TEM image of the aforementioned multi-element cathode material Q1 is shown below. Figure 2 As shown, by Figure 2 It can be seen that the multi-element cathode material Q1 shown includes the above-mentioned nickel-based multi-element material as a matrix, and a coating layer C1 covering the surface of the matrix.
[0185] The physical properties of the aforementioned multi-element cathode material Q1 are listed in Table 3.
[0186] Example 2
[0187] The method is the same as in Example 1, except that...
[0188] Step S4: Replace the above coating layer C1 with coating layer C2, and keep the other conditions the same to obtain the multi-element cathode material Q2.
[0189] The physical properties of the aforementioned multi-element cathode material Q2 are listed in Table 3.
[0190] Example 3
[0191] The method is the same as in Example 1, except that...
[0192] In step S3, the temperature of the third sintering is replaced with 890℃, while the other conditions remain the same, to obtain the multi-element cathode material Q3.
[0193] The physical properties of the aforementioned multi-element cathode material Q3 are listed in Table 3.
[0194] Example 4
[0195] The method is the same as in Example 1, except that...
[0196] Step S4: Replace the above coating layer C1 with coating layer C3, and keep the other conditions the same to obtain the multi-element cathode material Q4.
[0197] The physical properties of the aforementioned multi-element cathode material Q4 are listed in Table 3.
[0198] Example 5
[0199] The method is the same as in Example 1, except that...
[0200] Step S1: Replace the molar ratio of nickel salt (nickel sulfate), cobalt salt (cobalt sulfate), and manganese salt (manganese sulfate) with 75:10:15, while keeping all other conditions the same;
[0201] Step S2 yields the general formula [(Ni 0.75 Co 0.1 Mn 0.15 ) 0.999 Al 0.001 Multi-component precursors of (OH)2;
[0202] Step S3 yields the general formula Li 1.03 [(Ni 0.75 Co 0.1 Mn 0.15 ) 0.999 Al 0.001 ] 0.999 Zr 0.001 O2-based nickel-based multi-component materials;
[0203] Step S4 yields the multi-element cathode material Q5.
[0204] The physical properties of the aforementioned multi-element cathode material Q5 are listed in Table 3.
[0205] Example 6
[0206] The method is the same as in Example 1, except that...
[0207] Step S4: Replace the mass ratio of the above nickel-based multi-element material as the matrix and the above coating layer C1 with 100:0.25, while keeping the other conditions the same, to obtain the multi-element cathode material Q6.
[0208] The physical properties of the aforementioned multi-element cathode material Q6 are listed in Table 3.
[0209] Example 7
[0210] The method is the same as in Example 1, except that...
[0211] In step S4, the temperature of the first sintering is replaced with 700℃, while the other conditions remain the same, to obtain the multi-element cathode material Q7.
[0212] The physical properties of the aforementioned multi-element cathode material Q7 are listed in Table 3.
[0213] Example 8
[0214] The method is the same as in Example 1, except that...
[0215] Step S1: Replace the molar ratio of nickel salt (nickel sulfate), cobalt salt (cobalt sulfate), and manganese salt (manganese sulfate) with 90:5:5, while keeping all other conditions the same;
[0216] Step S2 yields the general formula [(Ni 0.9 Co 0.05 Mn 0.05 ) 0.999 Al 0.001 Multi-component precursors of (OH)2;
[0217] Step S3 yields the general formula Li 1.03 [(Ni 0.9 Co 0.05 Mn 0.05 ) 0.999 Al 0.001 ] 0.999 Zr 0.001 O2-based nickel-based multi-component materials;
[0218] Step S4 yields the multi-element cathode material Q8.
[0219] The physical properties of the aforementioned multi-element cathode material Q8 are listed in Table 3.
[0220] Example 9
[0221] The method is the same as in Example 5, except that...
[0222] In step S2, source M is added in a molar ratio of [n(M)] / [n(Ni)+n(Co)+n(Mn)] = 0.1, with all other conditions remaining the same, resulting in the general formula [(Ni 0.75 Co 0.1 Mn 0.15 ) 0.9 Al 0.1 Multi-component precursors of (OH)2;
[0223] Step S3 yields the general formula Li 1.03 [(Ni 0.75 Co 0.1 Mn 0.15 ) 0.9 Al 0.1 ] 0.999 Zr 0.001 O2-based nickel-based multi-component materials;
[0224] Step S4 yields the multi-element cathode material Q9.
[0225] The physical properties of the aforementioned multi-element cathode material Q9 are listed in Table 3.
[0226] Example 10
[0227] The method is the same as in Example 5, except that...
[0228] Step S3: Add the lithium source in a molar ratio of [n(Li)] / [n(Ni)+n(Co)+n(Mn)+n(M)+n(M')] = 1.1, with all other conditions remaining the same.
[0229] The general formula is Li 1.1 [(Ni 0.75 Co 0.1 Mn 0.15 ) 0.9 Al 0.1 ] 0.999 Zr 0.001 O2-based nickel-based multi-component materials;
[0230] Step S4 yields the multi-element cathode material Q10.
[0231] The physical properties of the aforementioned multi-element cathode material Q10 are listed in Table 3.
[0232] Example 11
[0233] The method is the same as in Example 1, except that...
[0234] Step S3: Source M' is added in a molar ratio of [n(M')] / [n(Ni)+n(Co)+n(Mn)] = 0.1, with all other conditions remaining the same.
[0235] The general formula is Li 1.03 [(Ni 0.93 Co 0.02 Mn 0.05 ) 0.999 Al 0.001 ] 0.9 Zr 0.1 O2-based nickel-based multi-component materials;
[0236] Step S4 yields the multi-element cathode material Q11.
[0237] The physical properties of the aforementioned multi-element cathode material Q11 are listed in Table 3.
[0238] Examples 12-14
[0239] The method is the same as in Example 1, except that...
[0240] Step S4: Replace the above coating layer C1 with coating layers C4-C6 respectively, while keeping the other conditions the same, to obtain the multi-element cathode materials Q12-Q14 respectively.
[0241] The physical properties of the aforementioned multi-element cathode materials Q12-Q14 are listed in Table 3.
[0242] Comparative Example 1
[0243] The method is the same as in Example 1, except that...
[0244] Step S1: Do not prepare a 0.1 mol / L source M solution;
[0245] Step S2, without adding source M solution, yields the general formula (Ni 0.93 Co 0.02 Mn 0.05 (OH)2 multi-component material precursor;
[0246] Step S3, without adding source M', yields the general formula Li. 103 Ni 093 Co 002 Mn 005 O2-based nickel-based multi-element materials are directly used as multi-element cathode materials, DQ1.
[0247] The XRD curve of the aforementioned multi-element cathode material DQ1 is shown below. Figure 1 As shown, by Figure 1 It can be seen that the multi-element cathode material DQ1 only has the characteristic peaks of multi-element materials.
[0248] The physical properties of the aforementioned multi-element cathode material DQ1 are listed in Table 3.
[0249] Comparative Example 2
[0250] The method is the same as in Example 1, except that step S4 is omitted.
[0251] Directly use the general formula Li in step S3 1.03 [(Ni 0.93 Co 0.02 Mn 0.05 ) 0.999 Al 0.001 ] 0.999 Zr 0.001 O2-based nickel-based multi-element materials are used as multi-element cathode materials, specifically DQ2.
[0252] The physical properties of the aforementioned multi-element cathode material DQ2 are listed in Table 3.
[0253] Comparative Examples 3-5
[0254] The method is the same as in Example 1, except that...
[0255] In step S4, the above-mentioned coating layer C1 is replaced with coating layers DC1-DC3 respectively, and the other conditions are the same, to obtain the multi-element cathode materials DQ3-DQ5 respectively;
[0256] The physical properties of the aforementioned multi-element cathode materials DQ3-DQ5 are listed in Table 3.
[0257] Table 3
[0258]
[0259]
[0260] Continued from Table 3
[0261]
[0262] Note: 3 - Mass ratio of matrix to coating layer.
[0263] Continued from Table 3
[0264]
[0265]
[0266] As can be seen from the results in Table 3, compared with Comparative Examples 1-5, the multi-element cathode materials prepared in Examples 1-14 include a nickel-based multi-element material with the composition shown in Formula II as a matrix, and a coating layer with the composition shown in Formula I covering the surface of the matrix; at the same time, the multi-element cathode materials prepared in Examples 1-14 have a crystal structure with α-NaFeO2 structure having R-3m space group, and the cell parameters satisfy:
[0267] The multi-element cathode materials prepared in Examples 1-14 were analyzed by XRD, and characteristic diffraction peaks of the (101) and (103) crystal planes of the coating layer were observed at 24-25.5° and 31-32.5°, respectively. In particular, by limiting the value of 0.0001 < I (103) / I (003) <0.005, 0.0001 <S (103) / S (003) <0.005, further improving the cycle life of multi-element cathode materials.
[0268] Test Example 1
[0269] The multi-element cathode materials (Q1-Q14 and DQ1-DQ5) prepared in Examples 1-14 and Comparative Examples 1-5 were used to assemble liquid pouch batteries. The specific steps are as follows:
[0270] The multi-component cathode material (Q1-Q14 and DQ1-DQ5), carbon nanotubes, Super P and polyvinylidene fluoride were dispersed in an appropriate amount of NMP at a mass ratio of 96.7:0.8:1.0:1.5. The mixture was coated on aluminum foil and dried. Then it was cut into cathode sheets of 112×40mm. The cathode sheets were then vacuum dried at 120℃ for 12h and then vacuum sealed for storage.
[0271] The negative electrode material, Super P, CMC, and SBR were dispersed in an appropriate amount of deionized water at a mass ratio of 96.5:0.5:1.2:1.8. The mixture was coated onto copper foil and dried, then cut into 112×40 mm negative electrode sheets. These sheets were then vacuum-dried at 105℃ for 12 hours and vacuum-sealed for storage. The separator was a 118×86 mm Celgard porous membrane. The electrolyte consisted of LiPF6 as the solute and equal volumes of ethylene carbonate, dimethyl carbonate, and diethyl carbonate as solvents, with a LiPF6 concentration of 1 mol / L.
[0272] The above-mentioned positive electrode, separator, negative electrode and electrolyte were assembled into liquid pouch batteries (W1-W14 and DW1-DW5) in a glove box filled with argon gas, where the water content and oxygen content were both less than 5 ppm.
[0273] The electrochemical performance of the above-mentioned liquid soft-pack battery was tested. The 0.1C and 1C capacity tests were conducted at a charge-discharge voltage of 3V-4.4V and a temperature of 25℃. The cycle test was conducted at a charge-discharge voltage of 2.8V-4.35V, a rate of 1C, and a temperature of 45℃. The test results are shown in Table 4.
[0274] The initial charge-discharge curves of the multi-element cathode materials in Example 1 and Comparative Example 1 in a liquid pouch battery are shown below. Figure 3 As shown, by Figure 3 It can be seen that, compared with Comparative Example 1, the multi-element cathode material in Example 1 has a higher charge and discharge capacity in the liquid pouch battery. That is, it shows that the pouch battery with the perovskite structure coating has a higher lithium-ion transport capability, which is beneficial to improving the rate performance of the multi-element material.
[0275] The cycle retention curves of the multi-element cathode materials in Example 1 and Comparative Example 1 in liquid pouch batteries are shown in the figure below. Figure 4 As shown, by Figure 4 As can be seen, compared with Comparative Example 1, the multi-element cathode material in Example 1 exhibits a higher cycle retention rate in the liquid pouch battery. This indicates that the coating layer is firmly bonded to the substrate, suppressing excessive changes in the crystal structure, mitigating structural distortion caused by lithium-ion insertion / extraction, maintaining a stable crystal structure, and improving the cycle life of the pouch battery. Notably, the liquid pouch battery charging voltage reaches as high as 4.35V, indicating that the coating layer can effectively suppress oxygen loss from the surface of the multi-element material, thereby improving the cycle life and safety of the multi-element cathode material.
[0276] Test Example 2
[0277] The difference from Test Example 1 is that the 118×86mm Celgard porous membrane (composed of PP / PE / PP three-layer membrane) was replaced with a 118×86mm polyethylene oxide (PEO) solid electrolyte membrane, and the electrolyte was no longer used, resulting in solid-state soft-pack batteries (W'1-W'14 and DW'1-DW'5).
[0278] The preparation steps of PEO solid electrolyte membrane are as follows: polyethylene oxide (PEO) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) are mixed in a mass ratio of 3:1, then hot-pressed to form a film with a thickness of 40 μm, and then vacuum dried at 60 °C for 10 h and then vacuum sealed for storage.
[0279] The electrochemical performance of the solid-state soft-pack battery was tested. The 0.1C and 0.2C capacity tests were conducted at a charge / discharge voltage of 3V-4.4V and a temperature of 55℃. The capacity retention test was conducted at a charge / discharge voltage of 2.8V-4.35V, a rate of 0.2C, 100 cycles, and a temperature of 55℃. The test results are shown in Table 4.
[0280] Table 4
[0281]
[0282]
[0283] As shown in Table 4, compared to Comparative Examples 1-5, the batteries assembled from the multi-element cathode materials of Examples 1-14 exhibit higher cycle life and capacity retention. Combined with the data in Tables 2-3, it can be seen that the cell parameter c of the coating layer in Examples 1-14 is smaller than the cell parameter c of the multi-element cathode material. This suppresses excessive expansion along the c-axis of the multi-element cathode material during charging, thereby preventing compressive stress on the surface of the material, inhibiting excessive changes in the crystal structure, mitigating lattice distortion caused by lithium-ion insertion / extraction, maintaining a stable crystal structure, and thus improving the cycle life and capacity retention of the multi-element cathode material.
[0284] Compared to Comparative Examples 2-5, the batteries assembled from the multi-element cathode material of Example 1 showed increased discharge capacities at 0.1C, 0.2C, and 1C rates. This indicates that the coating layer with Formula I exhibits excellent lithium-ion transport characteristics, suppresses side reactions between the multi-element cathode material and the electrolyte, and forms a stable CEI film, which is beneficial for improving the rate performance and cycle performance of the multi-element cathode material. Simultaneously, the coating layer with a layered perovskite phase (Formula I) has a high energy barrier, which can suppress oxygen loss from the surface of the multi-element cathode material, especially reducing oxygen loss caused by local overcharging, thus improving the safety of the cathode material.
[0285] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A multi-element cathode material, characterized in that, The multi-element cathode material includes a matrix and a coating layer covering the surface of the matrix; the matrix is a nickel-based multi-element material. The coating layer has the composition shown in Formula I: La 2-σ J σ Li p Al 1-p-q L q O 4-δ Formula I; In Formula I, J is selected from at least one element chosen from Ba, Sr, Sc, Y, Ce, Pr, Nd, Pm, Sm, and Eu; L is selected from at least one element chosen from Ni, Co, Mn, and Fe; and 0 ≤ σ <1, 0.4≤ p ≤0.7, 0.1≤ q ≤0.4, p + q <1, 0≤ δ <1; The matrix has the composition shown in Formula II: Li z [(Ni x Co y Mn 1-x-y ) 1-α M α [[ID=12>]] 1-β M' β O2 Formula II; In Formula II, M and M' are each independently selected from at least one element chosen from Al, Ba, Zr, Ti, Nb, Ta, Ga, Y, W, Ca, Sr, Sc, Cr, Mo, Hf, Si, Sm, V, La, Ce, Mg, and B; 0.9 ≤ z ≤1.3, 0< x <1, 0.01< y <1, x + y <1, 0< α ≤0.1, 0< β ≤0.1; The coating layer has an I4 / mm crystal structure with cell parameters satisfying: 3.6Å < a < 3.9Å, 12.5Å < c < 13.5Å; the multi-element cathode material has an α-NaFeO2 crystal structure with R-3m space group, with cell parameters satisfying: 2.86Å < a < 2.9Å, 14.1Å < c < 14.3Å. Wherein, the ionic conductivity of the coating layer is ≥0.3 mS / cm; Among them, the characteristic peak intensity I of the (103) crystal plane of the multi-element cathode material was measured by XRD. (103) The characteristic peak intensity I of the (003) crystal plane (003) The following relationship must be satisfied: 0.0001 < I (103) / I (003) <0.
005.
2. The multi-element cathode material according to claim 1, wherein, In Formula I, J is selected from at least one element chosen from Sr, Y, Ce, Pr, Nd, Pm, and Sm, L is selected from at least one element chosen from Ni, Co, and Mn, and 0.1 ≤ σ ≤0.6, 0.5≤ p + q ≤0.8, 0≤ δ <1; And / or, in Formula II, M and M' are each independently selected from at least one element selected from Al, Zr, Ti, Nb, Y, W, Sr, Mo, Hf, La, Ce, Mg, and B, 0.96 ≤ z ≤1.3, 0.7≤ x ≤0.95, 0.01≤ y ≤0.1, 0.71≤ x + y <1, 0.001≤ α ≤0.05, 0.001≤ β ≤0.
05.
3. The multi-element cathode material according to claim 1 or 2, wherein, Based on the mass of the substrate, the content of the coating layer is 0.01-2 wt%; And / or, the thickness of the coating layer is 2-20 nm; And / or, the median particle size D of the coating layer 50 ≤200nm; specific surface area ≥10m² 2 / g; And / or, the median particle size D of the multi-element cathode material 50 It is 2-30μm.
4. The multi-element cathode material according to claim 3, wherein, Based on the mass of the substrate, the content of the coating layer is 0.1-1 wt%; And / or, the ionic conductivity of the coating layer is 0.4-1 mS / cm; And / or, the thickness of the coating layer is 5-10 nm; And / or, the median particle size D of the coating layer 50 The specific surface area is 10-150 nm; the specific surface area is 20-500 m². 2 / g; And / or, the median particle size D of the multi-element cathode material 50 It ranges from 3 to 20 μm.
5. The multi-element cathode material according to claim 1 or 2, wherein, The multi-element cathode material was measured by XRD, and 2θ showed characteristic diffraction peaks of the (101) and (103) crystal planes of the coating layer at 24-25.5° and 31-32.5°.
6. The multi-element cathode material according to claim 5, wherein, The characteristic peak area S of the (103) crystal plane of the multi-element cathode material, as measured by XRD, is... (103) The characteristic peak area S of the (003) crystal plane (003) The following relationship must be satisfied: 0.0001 < S (103) / S (003) <0.
005.
7. The multi-element cathode material according to claim 6, wherein, The characteristic peak intensity I of the (103) crystal plane of the multi-element cathode material was measured by XRD. (103) The characteristic peak intensity I of the (003) crystal plane (003) The following relationship is satisfied: 0.001 < I (103) / I (003) <0.003; And, the characteristic peak area S of the (103) crystal plane of the multi-element cathode material as measured by XRD (103) The characteristic peak area S of the (003) crystal plane (003) The following relationship must be satisfied: 0.0001 < S (103) / S (003) <0.
003.
8. The multi-element cathode material according to claim 1 or 2, wherein, When the molar percentage x of Ni in the matrix satisfies 0.3 < x ≤ 0.98, the maximum change value Δc of the unit cell along the c-axis in the multi-element cathode material during charging and discharging is... max satisfy: Δc max = , where Δc max =c max c min Å; And / or, when the molar percentage x of Ni in the matrix satisfies 0.3 < x ≤ 0.98, the maximum change in shear strain of the multi-element cathode material during charging and discharging is... satisfy: = ,in, = .
9. The multi-element cathode material according to claim 8, wherein, When the molar percentage x of Ni in the matrix satisfies 0.3 < x ≤ 0.98, the maximum rate of change of the c-axis of the multi-element cathode material during charging and discharging is... satisfy: = Where c0 is the initial value of the unit cell along the c-axis, in Å; And / or, when the molar percentage x of Ni in the matrix satisfies 0.3 < x ≤ 0.98, the maximum rate of change of shear strain of the multi-element cathode material during charging and discharging is... satisfy: = Where (c / a)0 is the initial shear strain; And / or, the Δcmax and The measurement conditions are that the molar amount of lithium removed from the multi-element cathode material, Δz, is in the range of 0 < Δz < 0.9, where Δz is the amount of lithium ions removed from the multi-element cathode material during charging.
10. A method for preparing the multi-element cathode material according to any one of claims 1-9, characterized in that, The preparation method includes: mixing nickel-based multi-element materials as a matrix and a coating layer, performing a first sintering, a first crushing, and a first sieving to obtain a multi-element cathode material; The coating layer has the composition shown in Formula I: La 2-σ J σ Li p Al 1-p-q L q O 4-δ Formula I; In Formula I, J is selected from at least one element chosen from Ba, Sr, Sc, Y, Ce, Pr, Nd, Pm, Sm, and Eu; L is selected from at least one element chosen from Ni, Co, Mn, and Fe; and 0 ≤ σ <1, 0.4≤ p ≤0.7, 0.1≤ q ≤0.4, p + q <1, 0≤ δ <1; The matrix is a nickel-based multi-element material with the composition shown in Formula II: Li z [(Ni x Co y Mn 1-x-y ) 1-α M α 1-β M' β O2 Formula II; In Formula II, M and M' are each independently selected from at least one element chosen from Al, Ba, Zr, Ti, Nb, Ta, Ga, Y, W, Ca, Sr, Sc, Cr, Mo, Hf, Si, Sm, V, La, Ce, Mg, and B; 0.9 ≤ z ≤1.3, 0< x <1, 0< y <1, x + y <1, 0< α ≤0.1, 0< β ≤0.
1.
11. The preparation method according to claim 10, wherein, The mass ratio of the matrix to the coating layer is 100:0.01-2; And / or, the conditions for the first sintering include: a temperature of 270-620°C; The time is 4-48 hours.
12. The preparation method according to claim 11, wherein, The mass ratio of the matrix to the coating layer is 100:0.1-1; And / or, the conditions for the first sintering include: a temperature of 300-580°C; The time is 8-24 hours.
13. The preparation method according to claim 10, wherein, The coating layer is prepared according to the following steps: (1) The lanthanum source, J source, lithium source, aluminum source and L source are arranged according to n(La):n(J):n(Li):n(Al):n(L)=(2- σ ): σ : p: (1- p- q ): q The mixture is obtained by mixing the ingredients in a specific molar ratio. (2) The mixture is subjected to a first wet milling, a first drying, a second sintering, a second wet milling, a second drying, and a second crushing in sequence to obtain the coating layer.
14. The preparation method according to claim 13, wherein, The amount of lithium source used, calculated as Li, is n(Li) = (1.03 - 1.1) × p ; And / or, the first wet milling process includes: performing a first wet milling on the mixture, the first dispersant and the first solvent to obtain a first wet milling slurry; the second wet milling process includes: performing a second wet milling on the second sintered product, the second dispersant and the second solvent to obtain a second wet milling slurry.
15. The preparation method according to claim 14, wherein, The mass ratio of the mixture to the first dispersant is 100:0.001-5; the mass ratio of the second sintered product to the second dispersant is 100:0.001-5. And / or, the first dispersant and the second dispersant are each independently selected from dispersants with a weight-average molecular weight of 400-5000 g / mol; And / or, the particle size D of the first wet grinding slurry 50 <5μm, D 100 <20μm; And / or, the particle size D of the second wet grinding slurry 50 <0.5μm, D 100 <1μm.
16. The preparation method according to claim 15, wherein, The mass ratio of the mixture to the first dispersant is 100:0.005-2; the mass ratio of the second sintered product to the second dispersant is 100:0.005-2. And / or, the first dispersant and the second dispersant are each independently selected from polyacrylate and / or polyethylene glycol with a weight-average molecular weight of 400-5000 g / mol; And / or, the particle size D of the first wet grinding slurry 50 <0.5μm, D 100 <1μm; And / or, the particle size D of the second wet grinding slurry 50 <0.2μm, D 100 <0.5μm.
17. The preparation method according to claim 10 or 11, wherein, The nickel-based multi-element material is obtained according to the following steps: S1. Mix nickel salts, cobalt salts, and manganese salts according to the formula n(Ni):n(Co):n(Mn) = x : y :(1- xy Prepare a mixed salt solution by mixing the molar ratio of M source, precipitant, and complexing agent; prepare M source solution, precipitant solution, and complexing agent solution, respectively. S2. The mixed salt solution, M source solution, precipitant solution and complexing agent solution are added to the reaction vessel, and a co-precipitation reaction is carried out in an inert atmosphere. The resulting solid-liquid mixed slurry is filtered, washed, dried in the third stage and screened in the second stage. The resulting multi-component material precursor has the composition shown in Formula III. S3. The multi-component material precursor, lithium source and M' source are mixed, sintered, crushed and screened in the third step to obtain nickel-based multi-component material; Among them, [(Ni x Co y Mn 1-x-y ) 1-α M α Formula III (OH)2 18. The preparation method according to claim 17, wherein, The M source is added in an amount where the molar ratio is 0 < [n(M)] / [n(Ni)+n(Co)+n(Mn)] ≤ 0.1; And / or, in step S2, the conditions for the coprecipitation reaction include: pH value of 10-13; temperature of 40-80℃; and time of 5-50h; And / or, the particle size D of the multi-material precursor 50 2-30μm; And / or, in step S3, the lithium source is added in an amount with a molar ratio of 0.9≤n(Li) / [n(Ni)+n(Co)+n(Mn)+n(M)+n(M')]≤1.3; And / or, the M' source is added in an amount with a molar ratio of 0 < n(M') / [n(Ni)+n(Co)+n(Mn)] ≤ 0.1; And / or, the median particle size D of the M' source 50 ≤200nm; specific surface area ≥10m² 2 / g.
19. The preparation method according to claim 18, wherein, The M source is added in an amount with a molar ratio of 0.001 ≤ [n(M)] / [n(Ni) + n(Co) + n(Mn)] ≤ 0.05; And / or, in step S2, the conditions for the coprecipitation reaction include: pH value of 11-12; temperature of 50-70℃; and time of 8-32h; And / or, the particle size D of the multi-material precursor 50 3-20μm; And / or, in step S3, the lithium source is added in an amount with a molar ratio of 0.96≤n(Li) / [n(Ni)+n(Co)+n(Mn)+n(M)+n(M')]≤1.3; And / or, the M' source is added in an amount with a molar ratio of 0.001≤n(M') / [n(Ni)+n(Co)+n(Mn)]≤0.05; And / or, the median particle size D of the M' source 50 The surface area is 10-150 nm; the specific surface area is 50-500 m². 2 / g.
20. A lithium-ion battery, characterized in that, The lithium-ion battery includes the multi-element cathode material as described in any one of claims 1-9.
21. An electrical appliance, characterized in that, The electrical equipment includes the lithium-ion battery as described in claim 20.
Citation Information
Patent Citations
NCM ternary cathode material with recombinant La2nNi0.5Li0.5O4 and doped La<3+> on surface layer
CN109742375A
Positive electrode material and electrochemical device containing same
CN109860546A
Modified cobalt-free positive electrode material and preparation method and application thereof
CN115939350A
